Pengaruh Kualitas barang Terhadap Kepuasan Konsumen (Studi Kasus pada Toko Yoorihana Melalui Aplikasi Shopee) - Yona Melia (Universitas Labuhanbatu, 2022)
There are several factors that affect consumer satisfaction, one of which is the quality of the product. Based on the satisfaction assessment data at the Yoorihana store through the Shopee application, from 5 assessment scales, there are some consumers from the yoorihana store who provide less assessment of shopping satisfaction through the Shopee application so that the satisfaction assessment results at the store are not included in the best category. This study aims to determine the effect of product quality on consumer satisfaction in Yoorihana store through shopee application. This study used primary data obtained from the distribution of questionnaires containing 13 statements to 37 consumer samples. This study is descriptive, quantitative, and the influence of analysis in this study using simple linear regression analysis. The results showed that the variables on product quality had a significant influence on employee satisfaction of 41.6%.